Effects Of Laxatives On Postoperative Intestinal Sound Recovery - Wahyuni, Eko Sari; Hamarno, Rudi; Arif, Taufan; Astuti, Erlina Suci; Septiasih, Rossyana (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
Intestinal sound is produced by muscle movements in the digestive tract. The return of intestinal sound after surgery is an important indicator for patients to return to eating and drinking normally. This study aimed to determine whether the administration of laxatives before surgery can speed up the recovery of intestinal sound in patients undergoing surgery with general anesthesia. The study involved 30 patients divided into two groups: a laxative group and a control group. The laxative group received laxatives before surgery, while the control group did not. Intestinal sound recovery time was measured in both groups. The sampling technique uses purposive sampling with the Mann Whitney statistical test. The results showed that the administration of laxatives before surgery had a significant effect on intestinal sound recovery time in postoperative patients under general anesthesia (p < 0.05). The laxative group showed faster recovery of intestinal sound than the control group. From this study it can be concluded that the administration of pre-operative laxatives can be beneficial for postoperative patients under general anesthesia to accelerate the recovery of bowel function. So that suggestions to the next researcher are advised to conduct research respondents who are given more varied laxatives